The golden cage: heritage, (ethnic) Muslimness, and the place of Islam in post-Soviet Tatarstan. Issue 4 (20th October 2021) - Benussi, Matteo (Teo)
ABSTRACT: Through the Weber-inspired metaphor of the 'golden cage', this contribution discusses the dual process by which both Islamic heritage and secularity are produced in Russia's Muslim-majority Tatarstan Republic: on the one hand ('gold'), Islam is given visibility/legitimacy as an element of Russia's civilisational makeup; on the other ('cage'), the region's Islamic past is shaped by the state while 'excessive' manifestations of piety are marginalised. The contribution focuses on actors and dynamics at two heritage sites in post-Soviet Tatarstan – Kazan's kremlin and Qol Şärif mosque, and Şaxri Bolğar. The 'golden caging' of Islam, encapsulated in these two intensely cherished heritage projects, resonates with a significant number of Tatars who, owing in part to the republic's history of governmentalisation and populist mobilisation, embrace (or accept) a 'secular' model of ethnic, moral, and civic personhood.